Direct Vapor Growth of 2D Vertical Heterostructures with Tunable Band Alignments and Interfacial Charge Transfer Behaviors. Issue 7 (14th February 2019) - Zheng, Weihao; Zheng, Biyuan; Yan, Changlin; Liu, Ying; Sun, Xingxia; Qi, Zhaoyang; Yang, Tiefeng; Jiang, Ying; Huang, Wei; Fan, Peng; Jiang, Feng; Ji, Wei; et al.
Abstract: 2D vertical van der Waals (vdW) heterostructures with atomically sharp interfaces have attracted tremendous interest in 2D photonic and optoelectronic applications. Band alignment engineering in 2D heterostructures provides a perfect platform for tailoring interfacial charge transfer behaviors, from which desired optical and optoelectronic features can be realized. Here, by developing a two‐step chemical vapor deposition strategy, direct vapor growth of monolayer PbI2 on monolayer transition metal dichalcogenides (TMDCs) (WS2, WSe2, or alloying WS2(1− x ) Se2 x ), forming bilayer vertical heterostructures, is demonstrated. Based on the calculated electron band structures, the interfacial band alignments of the obtained heterostructures can be gradually tuned from type‐I (PbI2 /WS2 ) to type‐II (PbI2 /WSe2 ). Steady‐state photoluminescence (PL) and time‐resolved PL measurements reveal that the PL emissions from the bottom TMDC layers can be modulated from apparently enhanced (for WS2 ) to greatly quenched (for WSe2 ) compared to their monolayer counterparts, which can be attributed to the band alignment–induced distinct interfacial charge transfer behaviors. The band alignment nature of the heterostructures is further demonstrated by the PL excitation spectroscopy and interlayer exciton investigation. The realization of 2D vertical heterostructures with tunable band alignments will provide a new material platform for designing and constructing multifunctional optoelectronic devices. Abstract : Novel PbI2 /transition metal dichalcogenide (TMDC) (WS2, WSe2, or the alloying WS2(1 − x ) Se2 x ) vertical heterostructures are demonstrated using a two‐step chemical vapor deposition strategy. By tuning the x value, the band alignment of the heterostructures can be largely tuned from type‐I (PbI2 /WS2 ) to type‐II (PbI2 /WSe2 ), which show distinct charge transfer behaviors. These heterostructures deve‐lop a platform for designing and constructing multifunctional photonic and optoelectronic devices.